IN VITRO STUDIES ON THE ANTIDIABETIC ACTIVITY OF 2-THIOHYDANTOIN USING α-amylase AND α-GLUCOSIDASE - UMA S; DEVIKA PT (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of the present study was to investigate the inhibitory effect of 2-thiohydantoin on the enzymes α-amylase and α-glucosidase in vitro as an antidiabetic therapeutic approach to reduce gastrointestinal glucose production. Methods: Antidiabetic activity of the compound, 2-thiohydantoin was measured using the enzymes α-amylase and α-glucosidase. Results: Half-maximal inhibitory concentration of the antidiabetic α-amylase was found to be 410.35 μg/ml and α-glucosidase was found to be 356.33 μg/ml, respectively. Conclusion: The result obtained in the in vitro enzyme assay suggests the antidiabetic activity of 2-thiohydantoin.